Karakteristik Organoleptik Cookies Berbahan Dasar Hotong (Setaria italica) dengan Perbandingan Margarin dan Kenari (Canarium indicum) - Pays, Victory J; Tetelepta, Gilian; Moniharapon, Erynola (Universitas Pattimura, 2025)
The aim of this research was to determine the appropriate ratio of margarine and canarium to produce the best millet cookies based on organoleptic properties. This research used a Completely Randomized Design with five levels of substitution treatment for margarine and canarium (100%:0%, 75%:25%, 50%:50%, 25%:75%, 0%:100%). Cookies with a substitution of 0% margarine: 100% canarium were liked by the panelists in term of color, aftertaste, taste, texture and produced cookies with a light yellow color, a slight aftertaste, a slight canarium taste, a texture that did not crumble when pressed.